INTERACTIVE, MULTIFUNCTIONAL MIRROR – PART OF A SMART HOME - Paszkiel, Szczepan; Kania, Robert (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
This paper presents a possible implementation of a personal assistant and control interface for a smart home. A prototype is presented, featuring functions such as appliance and light control, a map system based on Google Maps and various informational data such as calendar entries and news. The device takes the form of a voice controlled mirror, allowing for integration in existing systems as a replacement for a common household item, without the need for additional space.